Amplifying accountability by benchmarking results at district and national levels. (11th December 2017) - Evans, Alice
Abstract: This multi‐level ethnography of the Zambian health system illustrates the importance of top‐down accountability, and how it has emerged in a historically neglected sector. Maternal healthcare indicators are prioritized when they are benchmarked, at district and national levels. The realization that Zambia was lagging behind African countries in making progress towards Millennium Development Goal (MDG) 5 (to reduce the maternal mortality ratio by three quarters) appears to have evoked reputational concerns and revealed inspirational possibilities. Growing prioritization also stems from a change in incentives, with some partner funding being conditional on the proportion of deliveries attended by skilled health personnel.